Roof Water Damage Prediction and Evaluation of Sand-Mud Sedimentary Tectonic Strata - Pengfei Jiang; Fumin Zhuge; Suolin Jing; Zongkai Li; Peng Xiao; Yuguang Lv (Geofluids)
The prediction and control of roof water disaster has been one of the key problems in the mining process of coal resources. With the increase of mining depth in the western mining area, the roof caving and communicating to the overlying water-bearing strata have led to an increasing number of roof water inrush accidents and deterioration of production environment of the working face. Aiming at the problem of roof water disaster prediction of sandy-argillaceous structural strata in Shanghaimiao mining area in China, firstly, the mechanical structure model of roof water inrush was built according to the parameters in the advance of the working face, and the thickness of the sandstone was used as the main controlling geological factor; the formula was derived for calculating the water-rich intensity Fzh of the overlying strata in the mining area. Secondly, starting from the height of the “Breakage-arch” development disturbance by combining the mechanical structure model of roof water inrush, the relative positional relation of the “Breakage-arch” and the water-bearing strata was analyzed, and a new method for judging the risk coefficient TW of roof water inrush was proposed. Finally, according to the geological drilling histogram and the field conditions of #111084 working face of the no. 1 mine in Shanghaimiao mine area, the water-rich index and water inrush risk coefficient of overlying water-bearing strata were obtained by means of discriminant analysis, and the water inrush risk of #111084 working face was evaluated and predicted quantitatively. The water-rich property evaluation of water-bearing strata under the condition of low degree of hydrogeological exploration was evaluated accurately and reasonably, and a new evaluation method of the water disaster during mining was proposed.